Web-Based Learning (WBL): a challenge for foreign languaje teachers - Quesada Pacheco, Allen (Actualidades Investigativas en Educación, 2005)
The vast majority of research in the past two decades on the use of computers in education has focused on knowledge acquisition and retention. The focus of this article is to investigate the issues of self-efficacy, attitude, and performance in online courses. Web-based learning will be the term used to describe this type of computer use. The review of literature inquires into the evolution of Computer-Assisted Language Learning towards an integrative approach that leads to Web-based learning. The benefits, components and challenges of Web-based Learning are addressed as well as how this type of approachexploits authentic practice of listening, speaking, reading and writing. This article also probes the relationship Web-based learning and achieving authenticity through the World Wide Web. En las últimas dos décadas se ha realizado una amplia gama de investigaciones sobre el uso de las computadores a nivel educativo con un enfoque hacia la adquisición y retención del conocimiento. Este artículo investiga temas claves sobre la eficacia, actitud y desarrollo de los cursos en línea. La terminología para describir este tipo de educación se conoce como instrucción mediada por Internet. El marco teórico de este artículo examina la evolución de la enseñanza por medio de Internet hacia una metodología integrada que dirige la enseñanza de un idioma con acceso al Internet. Se describen las características de la Instrucción por medio del Internet y como este tipo de Instrucción da soporte para la adquisición de la comprensión auditiva, la comunicación oral, la lectura comprensiva y la redacción. Se hace énfasis muy particular en la relación de la Instrucción en Línea y el desarrollo de autenticidad por medio del Internet.